Desain Phantom Air Untuk Kalibrasi CT Number dan Keseragaman CT Number Pada Pesawat CT Scan - Ary Kurniawati; Cholid Badri; Jeffri Ardiyanto (Jurnal Imejing Diagnostik (JImeD), 2015)
Background: Callibration of  CT number and uniformity is very important to the CT QC program particularly when the program aims to ensure that the CT Scanner equipment operates within the manufacturer's specifications. Since the commercial CT QC phantom is not always available or affordable in the department, a simple, easy and cheap modified CT water phantom design could be useful to support further regular departmental CT QC program.Purpose: (1) to design , a simple and an easy to handle of the modified CT water phantom,  and (2) to verify its callibration and measurement functions based on to the gold standard of a commercial CT water phantom.Methods: This study is an experimental research laboratories, where a modified design of  CT water phantom is then compared to the comercial gold standard CT water  phantom. The commercial CT water phantom uses a cylindrical phantom that contains water with various diameter in sizes. In the modified CT phantom design, it filled with water as well, where the three different size in phantom diameters (15 cm, 20 cm and 32 cm recpectively) created for specific measurement purpose that of the CT Number and uniformity CT Number.Results: Calliberating the function of the modified CT phantom design resulted in the three observasional data. For all different phantom diameters (15, 20 and 32 cm) showed some variation about their CT number and homogenity. Most of the callibration and homogenity tests of the CT number in water deemed significant (cal. CT number for the 20 cm and 32 diameter phantoms, 0,001 0,05 and sig. 0,04 0,05 respectively), instead of that the uniformity test  of the phantom sized with 20 cm in diameter (0,432 0,05).Conclussion: A modified water CT phantom designed with 20 cm in diameter could be used for measurement of the CT number uniformity. Yet, measurements of the CT number callibration and uniformity needed to be consider againts from a failed measurement due to the phantom problem design with sizes at 20 and 32 cm in diameters.